Bi-crosslinked cellulose gel electrolyte as well as preparation method and application thereof
Through the preparation of the bi-crosslinked cellulose gel electrolyte, the problems of insufficient mechanical strength and poor biodegradability of cellulose-based hydrogel electrolyte in the prior art are solved, and electrochemical materials with high stability and cyclability are achieved, which are suitable for aqueous zinc ion batteries and flexible electronic devices.
Patent Information
- Application Number
- CN202411880477.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing cellulose-based hydrogel electrolytes have problems such as insufficient mechanical strength, poor biodegradability and high processing costs in aqueous zinc ion batteries, and it is difficult to meet the needs of high stability, cyclability and high current density.
The preparation method of bi-crosslinked cellulose gel electrolyte is adopted to form a three-dimensional network structure with rich hydroxyl and carboxylic functional groups through the cross-linking reaction of Tempo oxidized nanocellulose and cellulose, thereby enhancing the mechanical and electrochemical properties of the material.
It achieves good mechanical properties, environmental friendliness and electrochemical stability of cellulose gel electrolyte, can effectively inhibit the growth and side reaction of zinc dendrites, and is suitable for aqueous zinc ion batteries and flexible electronic devices.
Smart Images

Figure CN119875148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science, and in particular relates to a double-crosslinked cellulose gel electrolyte and a preparation method and application thereof. Background Art
[0002] As the main representative type of electrochemical energy storage technology, rechargeable batteries play an indispensable role in the storage of renewable energy such as solar energy, wind energy, tidal energy and geothermal energy, thus meeting the urgent requirements of environmental friendliness and sustainable development. In recent years, rechargeable zinc-ion batteries have been widely used due to their high theoretical specific capacity (820 mAh g -1 ), low redox potential (standard hydrogen electrode is -0.763V), abundant reserves of metallic zinc, non-flammability and environmental friendliness, etc. However, the electrochemical performance of aqueous ZIBs is restricted by key issues such as dendrite growth, corrosion, hydrogen evolution reaction (HER), by-product generation and cathode dissolution. Hydrogel electrolytes have the advantages of wide operating voltage, good adsorption affinity, high ionic conductivity and relatively stable system, and are widely used in aqueous Zn-ion batteries.
[0003] Cellulose is the most abundant natural polymer material on earth, with the advantages of good thermal stability, excellent mechanical properties and low cost. Cellulose has been widely studied as a key component of hydrogel electrolytes for zinc-ion batteries. In addition to providing mechanical strength to prevent dendrite growth, the cellulose structure also helps to fix water molecules, thereby limiting the free water content and reducing interfacial side reactions. Currently, cellulose-based hydrogel electrolytes are often mixed with other synthetic polymers (such as polyacrylamide) to improve mechanical strength, but this approach limits the biodegradability of the material and increases processing costs. Therefore, it remains a challenge to develop a cellulose-based gel electrolyte for aqueous zinc-ion batteries with high stability, cyclability, and the ability to withstand high current densities. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a double cross-linked cellulose gel electrolyte.
[0005] Another object of the present invention is to provide a double cross-linked cellulose gel electrolyte prepared by the above method. The double cross-linked cellulose gel electrolyte uses cellulose as a base material, so that the gel electrolyte has good mechanical properties, environmental friendliness and electrochemical stability, and can be used in aqueous zinc ion batteries and other flexible electronic devices.
[0006] Another object of the present invention is to provide an application of the double cross-linked cellulose gel electrolyte.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a double cross-linked cellulose gel electrolyte comprises the following steps: preparing a Tempo oxidized nanocellulose dispersion and a cellulose solution respectively, then mixing the two, stirring them evenly, adding a chemical cross-linking agent to carry out a cross-linking reaction to obtain a cellulose gel, taking out the cellulose gel and soaking it in water to remove excess borax and CNF, and obtaining the double cross-linked cellulose gel electrolyte.
[0009] Preferably, the solid content (mass fraction) of the Tempo-oxidized nanocellulose dispersion is 1 to 5 wt %; and the solid content (mass fraction) of the cellulose solution is 1 to 5 wt %.
[0010] Preferably, the mass ratio of the cellulose in the cellulose solution, the Tempo-oxidized nanocellulose in the Tempo-oxidized nanocellulose dispersion, and the chemical cross-linking agent is 1:(0.04-0.5):(0.25-0.5).
[0011] Preferably, the chemical cross-linking agent is sodium tetraborate decahydrate (borax).
[0012] Specifically, the preparation method of the double cross-linked cellulose gel electrolyte comprises the following steps:
[0013] (1) dispersing absolutely dry cellulose in water, adding Tempo, sodium bromide and sodium hypochlorite in sequence, stirring at room temperature, adding sodium hydroxide solution dropwise to maintain the pH of the suspension at 10.5 to 11 until it no longer changes, and adding ethanol to terminate the reaction; then high-pressure homogenizing the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion;
[0014] (2) adding cellulose powder to an alkali / urea / water mixed solvent and stirring until no obvious solids are present to obtain a cellulose solution;
[0015] (3) mixing the Tempo oxidized nanocellulose dispersion obtained in step (1) with the cellulose solution obtained in step (2), stirring until completely mixed, then adding a chemical crosslinking agent, stirring vigorously to fully crosslink them, standing at room temperature, and soaking in water to remove excess CNF and sodium tetraborate decahydrate, thereby obtaining the dual crosslinked cellulose gel electrolyte.
[0016] The mass ratio of the absolute dry cellulose, Tempo and sodium bromide in step (1) is 10:(0.12-0.16):(0.8-1.2)
[0017] In the process of homogenizing and dispersing the nanocellulose in step (1), the homogenizing pressure is 20 to 70 MPa and the number of homogenization times is 5 to 30 times.
[0018] The stirring conditions described in step (2) are stirring for 3 h to 6 h at a temperature of -20°C to -15°C and a stirring speed of 500 r / min to 1500 r / min; and the mass fraction ratio of alkali, urea and water in the alkali / urea / water mixed solvent is 7:12:81.
[0019] The amount of cellulose added to the Tempo-oxidized nanocellulose dispersion in step (2) is 10 wt% to 32 wt%.
[0020] The stirring conditions described in step (3) are: stirring at a temperature of 25°C to 30°C for 10 min to 15 min, and a stirring speed of 500 r / min to 1500 r / min.
[0021] The standing condition described in step (3) is standing at room temperature for 24 hours to 36 hours.
[0022] The double-crosslinked cellulose gel electrolyte of the present invention can be used in aqueous zinc ion batteries and other flexible electronic devices.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] The present invention uses cellulose as a skeleton and Tempo-oxidized nanocellulose (CNF) as a filler and a reinforcing agent to carry out a cross-linking reaction to obtain a cellulose gel electrolyte. It contains abundant functional groups such as hydroxyl and carboxyl, forms a three-dimensional network structure, has good mechanical strength and a dynamic hydrogen bond cross-linking network, and can effectively inhibit zinc dendrite growth and side reactions.
[0025] The preparation method of the present invention is simple and efficient, the raw material cost is low and the source is wide, the prepared cellulose gel electrolyte has good mechanical properties, environmental friendliness and electrochemical stability, and can be used in aqueous zinc ion batteries and other flexible electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a scanning electron microscope image of the double cross-linked cellulose gel electrolyte prepared in Examples 1 to 4 of the present invention.
[0027] Figure 2 It is a comparison diagram of the tensile stress-strain curves of the double cross-linked cellulose gel electrolytes prepared in Examples 1 to 4 of the present invention.
[0028] Figure 3 is the ionic conductivity of the double cross-linked cellulose gel electrolyte prepared in Examples 1 to 4 of the present invention.
[0029] Figure 4The cyclic stability performance of zinc ion batteries installed with the double cross-linked cellulose gel electrolyte prepared in Example 1 of the present invention and the single cellulose borax cross-linked gel and single cellulose gel electrolyte is compared. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.
[0031] Example 1
[0032] A method for preparing a double cross-linked cellulose gel electrolyte comprises the following steps:
[0033] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in turn, slowly add 6.67mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion, the mass fraction (solid content) of nanocellulose in the dispersion is 1.6%; the homogenization pressure is 50Mpa, and the number of homogenizations is 5 times;
[0034] (2) 2.0 g of cellulose powder was dissolved in 48 g of a precooled (temperature: -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water was 7:12:81), and stirred for 3 h until the cellulose powder was completely dissolved to obtain a cellulose solution, wherein the mass fraction of cellulose in the system was 4%;
[0035] (3) At room temperature, 12.24 g of the Tempo oxidized nanocellulose dispersion obtained in step (1) was added to 50 g of the cellulose solution obtained in step (2), and the mixture was stirred rapidly until uniformly mixed. Then, 1 g of sodium tetraborate decahydrate was added and stirred vigorously for 15 minutes (at a speed of 800 r / min) to fully crosslink the cellulose.
[0036] Finally, the cellulose mixture was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 36 h to form a double-crosslinked cellulose gel, which was then immersed in deionized water to remove excess Tempo-oxidized nanocellulose and sodium tetraborate decahydrate to obtain a double-crosslinked cellulose gel electrolyte.
[0037] Example 2
[0038] A method for preparing a double cross-linked cellulose gel electrolyte comprises the following steps:
[0039] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.67mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion, the mass fraction (solid content) of nanocellulose in the dispersion is 1.6%; the homogenization pressure is 50Mpa, and the number of homogenizations is 5 times;
[0040] (2) 2.0 g of cellulose powder was dissolved in 48 g of a precooled (temperature: -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water was 7:12:81), and stirred for 3 h until the cellulose powder was completely dissolved to obtain a cellulose solution, wherein the mass fraction of cellulose in the system was 4%;
[0041] (3) At room temperature, 24.48 g of the Tempo oxidized nanocellulose dispersion obtained in step (1) was added to 50 g of the cellulose solution obtained in step (2), and the mixture was stirred rapidly until uniformly mixed. Then, 1 g of sodium tetraborate decahydrate was added and stirred vigorously for 15 minutes (at a speed of 800 r / min) to fully crosslink the cellulose.
[0042] Finally, the cellulose mixture was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 36 h to form a double-crosslinked cellulose gel, which was then immersed in deionized water to remove excess Tempo-oxidized nanocellulose and sodium tetraborate decahydrate to obtain a double-crosslinked cellulose gel electrolyte.
[0043] Example 3
[0044] A method for preparing a double cross-linked cellulose gel electrolyte comprises the following steps:
[0045] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.67mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion, the mass fraction (solid content) of nanocellulose in the dispersion is 1.6%; the homogenization pressure is 50Mpa, and the number of homogenizations is 5 times;
[0046] (2) 2.0 g of cellulose powder was dissolved in 48 g of a precooled (temperature: -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water was 7:12:81), and stirred for 3 h until the cellulose powder was completely dissolved to obtain a cellulose solution, wherein the mass fraction of cellulose in the system was 4%;
[0047] (3) At room temperature, 6.12 g of the Tempo oxidized nanocellulose dispersion obtained in step (1) was added to 50 g of the cellulose solution obtained in step (2), and the mixture was stirred rapidly until uniformly mixed. Then, 1 g of sodium tetraborate decahydrate was added and stirred vigorously for 15 minutes (at a speed of 800 r / min) to fully crosslink the cellulose.
[0048] Finally, the cellulose mixture was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 36 h to form a double-crosslinked cellulose gel, which was then immersed in deionized water to remove excess Tempo-oxidized nanocellulose and sodium tetraborate decahydrate to obtain a double-crosslinked cellulose gel electrolyte.
[0049] Example 4
[0050] A method for preparing a double cross-linked cellulose gel electrolyte comprises the following steps:
[0051] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.67mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion, the mass fraction (solid content) of nanocellulose in the dispersion is 1.6%; the homogenization pressure is 50Mpa, and the number of homogenizations is 5 times;
[0052] (2) 2.0 g of cellulose powder was dissolved in 48 g of a precooled (temperature: -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water was 7:12:81), and stirred for 3 h until the cellulose powder was completely dissolved to obtain a cellulose solution, wherein the mass fraction of cellulose in the system was 4%;
[0053] (3) At room temperature, 12.24 g of the Tempo oxidized nanocellulose dispersion obtained in step (1) was added to 50 g of the cellulose solution obtained in step (2), and the mixture was stirred rapidly until uniformly mixed. Then, 0.5 g of sodium tetraborate decahydrate was added and stirred vigorously for 15 minutes (at a speed of 800 r / min) to fully crosslink the cellulose.
[0054] Finally, the cellulose mixture was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 36 h to form a double-crosslinked cellulose gel, which was then immersed in deionized water to remove excess Tempo-oxidized nanocellulose and sodium tetraborate decahydrate to obtain a double-crosslinked cellulose gel electrolyte.
[0055] The scanning electron microscopy images of the double cross-linked cellulose gel electrolytes prepared in Examples 1 to 4 are as follows: Figure 1 As shown, it can be clearly seen from the figure that the double-crosslinked cellulose gel electrolyte prepared by the present invention has a rich spatial network structure constructed by cellulose, which can promote the transmission of zinc ions inside the electrolyte.
[0056] The tensile stress-strain curve comparison of the double cross-linked cellulose gel electrolytes prepared in Examples 1 to 4 is shown in FIG. Figure 2 As shown in the figure, the test method is to use a tensile compression material testing machine (INSTRON 5565, USA) to perform tensile tests on the samples. The tensile specimen is rectangular, the gauge length is set to 20 mm, and the tensile / compression rate is 2 mm / min. Each sample is tested 5 to 7 times and the average value is taken. Figure 2 It can be seen that the double cross-linked cellulose gel electrolytes of Examples 1 to 4 all have good tensile properties. Among them, Examples 1 and 2 have higher tensile deformation limits due to the large amount of nanocellulose added, but the tensile stress limit of Example 2 is reduced due to the excessively high nanocellulose content; Example 3 has a small amount of nanocellulose added and the chemical cross-linking agent content of Example 4 is insufficient, so the tensile properties of both are slightly inferior to those of Examples 1 and 2.
[0057] The ionic conductivity of the double cross-linked cellulose gel electrolyte prepared in Examples 1 to 4 is as follows: Figure 3 As shown in the figure, the test method is to assemble the battery in the order of stainless steel sheet, gel electrolyte, and stainless steel sheet, and use an electrochemical workstation (CHI 660E) to perform an alternating current impedance test (EIS) to calculate the ionic conductivity. Figure 3 It can be seen that the double-crosslinked cellulose gel electrolytes prepared in Examples 1 to 4 have higher ionic conductivity, better electrochemical properties, and can promote the transmission of zinc ions.
[0058] Figure 4 The cyclic stability performance of zinc ion batteries installed with double cross-linked cellulose gel electrolyte prepared in Example 1 of the present invention and single cellulose borax cross-linked gel and single cellulose gel electrolyte is compared. The test method is to use a blue battery detection system (CT2001A) to perform a cyclic constant current charge and discharge test on the Zn||electrolyte||Zn symmetrical battery.
[0059] Among them, the preparation method of the single cellulose borax cross-linked gel is as follows: 2.0g of cellulose powder is dissolved in 48g of a pre-cooled (temperature is -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water is 7:12:81), and stirred for 3h until the cellulose powder is completely dissolved to obtain a cellulose solution, wherein the mass fraction of cellulose in the system is 4%; under room temperature conditions, 1g of sodium tetraborate decahydrate is added to 50g of the cellulose solution and stirred vigorously (the speed is 800r / min) to fully cross-link the cellulose; finally, the cellulose mixture is poured into a polytetrafluoroethylene mold, and allowed to stand at room temperature for 36h to form a cellulose gel, which is then immersed in deionized water to remove excess sodium tetraborate decahydrate to obtain a single cellulose borax cross-linked gel.
[0060] Preparation method of single cellulose gel: dissolve 2.0g cellulose powder in 48g pre-cooled (temperature is -15°C) sodium hydroxide / urea / deionized water mixed solvent (the mass ratio of sodium hydroxide / urea / deionized water is 7:12:81), stir for 3h until the cellulose powder is completely dissolved to obtain a cellulose solution, and the mass fraction of cellulose in the system is 4%; at room temperature, pour the cellulose solution into a polytetrafluoroethylene mold and let it stand at room temperature for 36h to form a cellulose gel.
[0061] from Figure 4 It can be seen that when the single cellulose gel is used without adding any reinforcing agent and cross-linking agent, the assembled zinc-zinc symmetrical battery cannot operate stably after cycling for 50 hours; the single cellulose borax cross-linked cellulose gel adds a chemical cross-linking agent on the basis of the former, which enhances the stability of the structure, so that the zinc-zinc symmetrical battery installed therein can be stably cycled for 150 hours; the double cross-linked cellulose gel electrolyte prepared in Example 1 adds Tempo oxidized nanocellulose dispersion and a chemical cross-linking agent, which enhances the stability of its fiber skeleton network and increases the ion transmission channel, so that the zinc-zinc symmetrical battery prepared therein can be stably cycled for more than 1000 hours.
[0062] In summary, the double cross-linked cellulose gel electrolyte prepared in the embodiment of the present invention has excellent comprehensive performance. After actual testing, the gel electrolyte has abundant hydroxyl and carboxyl functional groups, forming a three-dimensional network structure. It has good mechanical and electrochemical properties and has good electrochemical application prospects. The raw material components of the gel electrolyte are safe and the process manufacturing cost is low, which is conducive to industrialization and large-scale promotion and application.
[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a double cross-linked cellulose gel electrolyte, characterized in that: The method comprises the following steps: preparing Tempo oxidized nanocellulose dispersion and cellulose solution respectively, then mixing the two, stirring them evenly, adding a chemical crosslinking agent to carry out a crosslinking reaction to obtain a cellulose gel; and soaking the cellulose gel in water to obtain the double crosslinked cellulose gel electrolyte.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the cellulose in the cellulose solution, the Tempo-oxidized nanocellulose in the Tempo-oxidized nanocellulose dispersion, and the chemical crosslinking agent is 1:(0.04-0.5):(0.25-0.5).
3. The preparation method according to claim 1, characterized in that: The chemical cross-linking agent is sodium tetraborate decahydrate.
4. The preparation method according to claim 1, characterized in that: The Tempo-oxidized nanocellulose dispersion has a solid content of 1 to 5 wt %.
5. The preparation method according to claim 1, characterized in that: The solid content of the cellulose solution is 1-5 wt %.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dispersing absolutely dry cellulose in water, adding Tempo, sodium bromide and sodium hypochlorite in sequence, stirring at room temperature, adding alkali solution dropwise to maintain the pH of the suspension at 10.5 to 11 until it no longer changes, and adding ethanol to terminate the reaction; then high-pressure homogenizing the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion; (2) adding cellulose powder to an alkali / urea / water mixed solvent and stirring until no obvious solids are present to obtain a cellulose solution; (3) mixing the Tempo oxidized nanocellulose dispersion obtained in step (1) with the cellulose solution obtained in step (2), stirring until completely mixed, then adding a chemical crosslinking agent, stirring to fully crosslink, standing at room temperature, and finally soaking in water to obtain the dual crosslinked cellulose gel electrolyte.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the absolute dry cellulose, Tempo and sodium bromide described in step (1) is 10: (0.12-0.16): (0.8-1.2); in the process of homogenizing and dispersing the nanocellulose described in step (1), the homogenizing pressure is 20-70 MPa and the number of homogenization times is 5-30 times.
8. The preparation method according to claim 6, characterized in that: The stirring conditions described in step (2) are stirring at a temperature of -20°C to -15°C for 3h to 6h and a stirring speed of 500r / min to 1500r / min; The stirring conditions described in step (3) are: stirring at a temperature of 25° C. to 30° C. for 10 min to 15 min, and a stirring speed of 500 r / min to 1500 r / min; The standing condition described in step (3) is standing at room temperature for 24 hours to 36 hours.
9. A double cross-linked cellulose gel electrolyte prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the double cross-linked cellulose gel electrolyte according to claim 9 in aqueous zinc ion batteries or flexible electronic devices.
Citation Information
Patent Citations
TEMPO oxidized nanocellulose-based composite hydrogel and preparation method thereof
CN114044919A
Preparation method of cellulose-based gel electrolyte
CN115440505A
Wood fiber flexible monatomic carbon aerogel as well as preparation method and application thereof
CN118545695A
Method for producing cellulose nanofiber dispersion liquid
JP2014118521A
Production method of cellulose gel, and cellulose gel
JP2018104314A